2-Year Outcome of a New Modified Luque Trolley Technque versus Traditional Growing Rods in the Management of Progressive Juvenile Onset Scoliosis. Issue 1 (April 2016) - Cottam, Andrew; Van Herwijnen, Bart; Davies, Evan
Introduction: Our objective was the long term evaluation of a new growth guidance technique compared with growing rods for posterior instrumentation of scoliosis. We performed a retrospective review of patient records and radiological imaging. A traditional Luque Trolley construct uses wires to hold growth guidance rods together. We describe a new technique which uses Domino end to side connectors in place of the wires with the aim of providing a stronger construct to limit curve progression. From a group of 28 patients treated with this technique we review 23 patients with a minimum of 2 year follow up. The mean age at surgery was 7.3 years (10 Male and 18 Female). The mean pre-operative Cobb angle was 69.1 degrees. All patients had posterior correction and modified Luque trolley construct with domino. We compared this to a group of 6 patients with a minimum 2 year follow up who were treated with growing rods. The mean age of this group was 7 years (2 Male 4 Female). The mean pre-operative Cobb angle was 56.5 degrees. All of these patients had posterior correction with growing rods. Materials and Methods: Sequential measurement of Cobb angle and length of rods was performed, with recording of further surgical procedures and associated complications. This enabled us to demonstrate curve progression and growth of the construct in both patient groups. Results: In the domino group the mean pre-operative curve was 69.1 degrees corrected to a mean post-operative angle of 36 degrees showing a mean percentage correction of 48.9%. This compared with a mean pre-operative curve of 56.5 degrees in the growing rods group, which was corrected to a mean post-operative angle of 36.1 degrees showing a mean percentage correction of 41.3%. In both groups the curves progressed despite surgery with a mean progression of 10.9 degrees after 1 year and 15.7 degrees at year 2 in the domino group and a mean progression of 3.3 degrees after year 1 and 14.9 degrees at year 2 in the growing rod group. In both groups the constructs had limited growth. The mean amount of growth at 2 years was 3.7mm ( 0. 19cm per year) in the domino group and 10.8mm ( 0.54cm per year) in the growing rod group. Conclusion: Both techniques do not completely prevent progression of scoliosis. Our new domino technique demonstrates as good a capacity for initial curve correction and limiting further curve progression as a growing rod technique but has a more limited capacity for further longitudinal growth. However the new domino technique is vastly cheaper and avoided a mean of 3.4 surgeries in the 2 year period compared with the growing rods.